Description of a new species of the hippolytid shrimp genus Eualus Thallwitz, 1892 from Japan, and clarification of the status of E. kikuchii Miyake & Hayashi, 1967 (Crustacea: Decapoda: Caridea) - Komai, Tomoyuki; Fujiwara, Yoshihiro (Zootaxa, 2012)
This study reports on two species of the hippolytid shrimp genus Eualus Thallwitz, 1892 from Japan. The first, Eualusctenomerus n. sp., is described on the basis of six specimens from off southern Kyushu. The new species appears closestto E. cteniferus (Barnard, 1950) from South Africa, E. drachi Noël, 1978 from the Mediterranean, E. lebourae Holthuis,1951 from the eastern Atlantic, and E. pectiniformis Hanamura, 2008 from southeastern Australia. The second is referredto E. kikuchii Miyake & Hayashi, 1967, which has been considered to be synonymous with E. bulychevae Kobjakova,1955, described from the South Kuril Islands, Far East Russia. Eualus kikuchii is redescribed as a valid species on thebasis of the holotype and additional specimens from various Japanese localities. Both species occurred in the whale-fall ecosystems located off Cape Nomamisaki, Kyushu, Kagoshima Prefecture.